KH. FAQIH USMAN: VISI POLITIK SEORANG ULAMA - Arifin Suryo Nugroho (Khazanah Pendidikan, 2020)
ABSTRACTKH. Faqih Usman was one of the best cadres of Muhammadiyah as well asMuhammadiyah's General Chairperson for the 1961-1971 term, although that positionwas only held for a few days because after his inauguration he later died on October 3,1968. He was a person who inspired Muhammadiyah and the Indonesian Nation. Theformer MIAI management and member of the Central National Committee had the roleof upholding the republic during the struggle for independence. Active in the Masyumiorganization and as a former Minister of Religion during the Halim PerdanakusumahCabinet, made him feel responsible when the PRRI eruption broke out. He along withM. Roem, struggled as hard as a mediator to reconcile the conflict between PRRI andthe central government at that time. This research uses the historical research method,which consists of four stages namely heuristics, criticism, interpretation, andhistoriography. The author uses a biographical approach to see figures in theirhistorical framework.Keywords: political biography, Muhammadiyah figures, Muhammadiyah history